First Occurrence of the Crustacean Ergasilus ogawai from Gills of Four Species of Fishes in Iraq - Abbas, T.K A; Balasem, A. N; Khamees, N. R (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
For the first time in Iraq, the crustacean Ergasilus ogawai Kabata, 1992 was recorded from the gills of Silurus triostegus, Mastacembelus mastacembelus, Mystus pelusius and Acanthopagrus latus out of 12 fish species caught from Garmat Ali river north of Basrah city during the period from September 1999 till August 2000. The percentage incidence of infestations of these four fish species were 98.9%, 100%, 49.6% and 71.4% while the intensity of infestations were 417, 81.8, 3.4 and 2, respectively. No significant differences in infestations of male and female hosts with this crustacean were detected.